The Influence Of Financial Socialization, Overconfidence And Mental Accounting On Investment Decisions - I Gede Adiputra; Nur Ainun Bangun; Bella Graceilla (Jurnal Manajemen, 2024)
This study examines the effect of financial socialisation, herding, overconfidence and mental accounting on investment decisions among stock investors in Jakarta. The sample in the study is stock investors who reside in Jakarta.   The purposive sampling method collected 205 respondents through Google Forms distributed online on social media. The research data were analysed with a structural equation system using SmartPLS.3.2.9 software. The results showed that financial socialisation positively and significantly influences Generation Z's investment decisions in Jakarta. Overconfidence positively and significantly influences Generation Z's investment decisions in Jakarta. Mental accounting has a positive and significant influence on the investment decisions of Generation Z in Jakarta.